Countering radicalism: Text analysis on online da’wah in Indonesia - Maknun, Moch Lukluil; Iswanto, Agus; Hidayat, Roch Aris; Hasfi, Nurul; Islahuddin, Islahuddin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - The purpose of this study is to observe Kyai Ma'ruf Khozin's online da'wah.Method - This research uses data triangulation and qualitative text analysis to understand da'wah narratives and focus group discussions on exploring discourse production. In addition to the main informants, we also conducted snowballing in-depth interviews with related parties.Result - The research findings show that Kyai Ma'ruf Khozin is a Kyai who actively produces moderate Muslim discourse. He has a motive to counter misconceptions about Islamic values discussed within the Muslim community. He also intends to develop moderate Islamic teachings, both to strengthen the practices of NU citizens and to counter conservative and radical Islamic values.Implication – The implication of this study is that it requires the awareness of moderate preachers who have the authority to develop da'wah in online media.Originality/Value - the specialty of this study is one of the best practices of moderate da'wah on Facebook media, which is the simplest media and reaches all da'wah circles.***Tujuan - Tujuan dari penelitian ini adalah untuk mengamati dakwah online Kyai Ma'ruf Khozin.Metode - Penelitian ini menggunakan triangulasi data dan analisis teks kualitatif untuk memahami narasi dakwah dan diskusi kelompok terarah untuk mengeksplorasi produksi wacana. Selain informan utama, kami juga melakukan wawancara mendalam secara snowball dengan pihak-pihak terkait.Hasil - Temuan penelitian menunjukkan bahwa Kyai Ma'ruf Khozin adalah seorang Kyai yang aktif memproduksi wacana Muslim moderat. Ia memiliki motif untuk melawan kesalahpahaman tentang nilai-nilai Islam yang didiskusikan dalam komunitas Muslim. Ia juga bermaksud mengembangkan ajaran Islam moderat, baik untuk memperkuat praktik-praktik warga NU maupun untuk melawan nilai-nilai Islam yang konservatif dan radikal.Implikasi - Implikasi dari penelitian ini adalah perlunya kesadaran para dai moderat yang memiliki otoritas untuk mengembangkan dakwah di media online.Orisinalitas/Nilai - Keistimewaan penelitian ini adalah salah satu praktik terbaik dakwah moderat di media Facebook, yang merupakan media paling sederhana dan menjangkau semua kalangan dakwah.